The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.3201/eid1312.070527
|View full text |Cite
|
Sign up to set email alerts
|

Changing Epidemiology of Human Brucellosis, Germany, 1962–2005

Abstract: This endemic occupational disease has become a foodborne and travel-associated zoonosis primarily affecting Turkish immigrants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
89
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 26 publications
(32 reference statements)
3
89
0
2
Order By: Relevance
“…Brucellosis causes systemic symptoms, most often fever and malaise, and can involve many organs. Osteoarticular manifestations are frequent focal complications (Al Dahouk et al, 2007a). As observed in other Balkan countries, the male population accounted for most cases of brucellosis reported in Bosnia and Herzegovina (71 %) and infection resulted from occupational exposure (Obradović & Velić, 2010).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Brucellosis causes systemic symptoms, most often fever and malaise, and can involve many organs. Osteoarticular manifestations are frequent focal complications (Al Dahouk et al, 2007a). As observed in other Balkan countries, the male population accounted for most cases of brucellosis reported in Bosnia and Herzegovina (71 %) and infection resulted from occupational exposure (Obradović & Velić, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Accordingly, B. melitensis strains isolated in Germany are most often of the East Mediterranean genotype (Al Dahouk et al, 2007b). As was the case here, onset of symptoms often occurs after the end of the German summer holiday season (August/ September) and coincides with the return of immigrants from disease-endemic countries where the peak of human brucellosis cases is in June and July (Al Dahouk et al, 2007a).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…22 However, some studies have suggested a recent shift in the epidemiology of brucellosis from rural to urban settings, possibly related to unpasteurized milk consumption in urban environments. 39,40 A high Brucella seroprevalence among cattle in smallholder dairy systems in the Moshi area suggests that this sector may be a possible source of infection for the urban population. 18 With a larger sample size, an association between brucellosis and site of residence, socio-economic status, or tribe may have been observed.…”
Section: Discussionmentioning
confidence: 99%